Risk of injuries in Paralympic track and field differs by impairment and event discipline - Blauwet, C. A.; Cushman, D.; Emery, C.; Willick, S. E.; Webborn, N.; Derman, W.; Schwellnus, M.; Stomphorst, J.; Van de Vliet, P. (The American Journal of Sports Medicine, 2016)
Background: The incidence rates (IRs) and factors associated with injuries in the sport of Paralympic athletics (track and field) have not been comprehensively and prospectively studied. Purpose: To determine injury IRs, characteristics of injuries, and associated factors in the sport of athletics at the London 2012 Paralympic Games. Study Design: Cohort study; Level of evidence, 2. Methods: A total of 977 athletes competing in the sport of athletics were followed over a total 10-day competition period of the Paralympic Games. Daily injury data were obtained via 2 databases: (1) a custom-built, web-based injury and illness surveillance system (WEB-IISS), maintained by team medical personnel; and (2) the organizing committee database, maintained by medical providers in the medical stations operated by the London Organising Committee of the Olympic and Paralympic Games. Athlete impairment and event discipline were obtained via the International Paralympic Committee athlete database. IRs (injuries per 1000 athlete-days) by impairment, event discipline, sex, and age were examined. Results: The overall IR was 22.1 injuries per 1000 athlete-days (95% CI, 19.5-24.7). In track disciplines, ambulant athletes with cerebral palsy experienced a lower incidence of injuries (IR, 10.2; 95% CI, 4.2-16.2) when compared with ambulant athletes from other impairment categories. Athletes in seated throwing experienced a higher incidence of injuries (IR, 23.7; 95% CI, 17.5-30.0) when compared with athletes in wheelchair racing (IR, 10.6; 95% CI, 5.5-15.6). In both track and field disciplines, the majority of injuries did not result in time loss from competition or training. Ambulant athletes experienced the greatest proportion of injuries to the thigh (16.4% of all injuries; IR, 4.0), observed predominantly in track athletes. Wheelchair or seated athletes experienced the greatest proportion of injuries to the shoulder/clavicle (19.3% of all injuries; IR, 3.4), observed predominantly in field athletes. Conclusion: This is the first prospective cohort study examining injury IRs and associated factors in the sport of athletics at the Paralympic Games. Injury patterns were specific to the event discipline and athlete impairment. The majority of injuries occurred to the thigh (ambulant athletes) or shoulder/clavicle (wheelchair or seated athletes) and did not result in time loss.